Impact of strategies to reduce polypharmacy on clinically relevant endpoints: a systematic review and meta‐analysis. (7th May 2016) - Johansson, Tim; Abuzahra, Muna E.; Keller, Sophie; Mann, Eva; Faller, Barbara; Sommerauer, Christina; Höck, Jennifer; Löffler, Christin; Köchling, Anna; Schuler, Jochen; Flamm, Maria; Sönnichsen, Andreas
Abstract : Aim: The aim of the present study was to explore the impact of strategies to reduce polypharmacy on mortality, hospitalization and change in number of drugs. Methods: Systematic review and meta‐analysis: a systematic literature search targeting patients ≥65 years with polypharmacy (≥4 drugs), focusing on patient‐relevant outcome measures, was conducted. We included controlled studies aiming to reduce polypharmacy. Two reviewers independently assessed studies for eligibility, extracted data and evaluated study quality. Results: Twenty‐five studies, including 10 980 participants, were included, comprising 21 randomized controlled trials and four nonrandomized controlled trials. The majority of the included studies aimed at improving quality or the appropriateness of prescribing by eliminating inappropriate and non‐evidence‐based drugs. These strategies to reduce polypharmacy had no effect on all‐cause mortality (odds ratio 1.02; 95% confidence interval 0.84, 1.23). Only single studies found improvements, in terms of reducing the number of hospital admissions, in favour of the intervention group. At baseline, patients were taking, on average, 7.4 drugs in both the intervention and the control groups. At follow‐up, the weighted mean number of drugs was reduced (−0.2) in the intervention group but increased (+0.2) in controls. Conclusions: There is no convincing evidence that the strategies assessed in the present review are effective in reducing polypharmacy or have an impact on clinically relevant endpoints. Interventions are complex; it is still unclear how best to organize and implement them to achieve a reduction in inappropriate polypharmacy. There is therefore a need to develop more effective strategies to reduce inappropriate polypharmacy and to test them in large, pragmatic randomized controlled trials on effectiveness and feasibility.